Performing Nashville : Music Tourism and Country Music's Main Street - Fry, Robert W. (Leisure Studies in a Global Era, 2017)
This book explores the formation and continuance of Nashville, Tennessee as a music place, the importance of the fans (tourists) in creating Nashville's multifaceted musical identity, and the music and city's influence on the formation and performance of the individual and collective identities of the country-music fan. More importantly, the author discusses the larger issue of country music as a signifier of tradition suggesting that for many visitors, the music serves as a soundtrack, while Nashville serves as a performative space that permits the creation, performance, and remembrance of not only the country-music tradition, but also various individual and collective traditions and an idealized American identity. Through the theatrics of tourism, Nashville and its connection to country music are performed daily, reinforced through the sound and landscape of country music. Performing Nashville will be of interest to students and scholars across a range of disciplines, including tourism studies, leisure studies, ethnomusicology, sociology, folklore and anthropology.- Resumé vydavatel